Leptospira spp. and Brucella ovis seroprevalence in sheep: preliminary results of one year surveillance program - BERTELLONI, F.; TURCHI, B.; CERRI, D.; PINZAUTI, P.; FRATINI, F. (Journal of the Hellenic Veterinary Medical Society, 2018)
In order to assess the diffusion of brucellosis by Brucella ovis and leptospirosis in sheep flocks in Tuscany, 410 blood samples were collected from males of 76 breeding farms from January to December 2015. All sera resulted negative for B. ovis. A percentage of 17.80% sera was found positive for Leptospira spp. Among all breeding farms, 34.21% resulted positive. The most represented serovars were Pomona (6.34%), Hardjo (4.14%), Grippotyphosa (3.17%) and Bratislava (1.70%). The highest antibody titers were detected for serovar Hardjo (1:25600) and serovars Pomona and Grippotyphosa (1:1600). These results confirm the role of sheep as maintenance host for serovar Hardjo and highlight the spreading of serovar Grippotyphosa in the study area. Constant field investigation, especially on farm animals, could be useful to determine trends and diffusion of some occupational re-emerging diseases, such as leptospirosis.